2007
DOI: 10.1007/978-3-540-68908-9
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Radiology

Abstract: Why write a book on emergency radiology? In many countries, hospital emergency departments have become a major part of the healthcare safety net. In the last decade economically-driven structural changes in health care delivery have caused a dramatic increase in emergency department visits. In response to capacity and staffing pressures, hospitals are developing and implementing a variety of strategies designed to improve patient flow and reduce overcrowding in the emergency department. Several factors are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 217 publications
(338 reference statements)
0
3
0
Order By: Relevance
“…Delayed post traumatic rupture of the spleen is an unusual outcome and has been reported to occur between two and 70 days post trauma (mostly happens 4 - 8 days post injury) (2-4). Along with pseudocysts, abscesses, and pseudoaneurysms, delayed splenic rupture (DSR) is considered as a complication of splenic injuries (3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delayed post traumatic rupture of the spleen is an unusual outcome and has been reported to occur between two and 70 days post trauma (mostly happens 4 - 8 days post injury) (2-4). Along with pseudocysts, abscesses, and pseudoaneurysms, delayed splenic rupture (DSR) is considered as a complication of splenic injuries (3).…”
Section: Introductionmentioning
confidence: 99%
“…Although DSR is defined as bleeding more than 48 hours after blunt trauma in a previously hemodynamically stable patient (4, 5), a review of the reported cases in the literature shows that in almost all of the cases the initial multidetector computed tomography (MDCT) imaging has revealed some form of damage to the spleen. The importance of delayed splenic rupture lies in its significantly higher mortality rate (5% - 15%), compared with the 1% overall mortality for acute splenic injuries (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation